2008
DOI: 10.1002/bdm.621
|View full text |Cite
|
Sign up to set email alerts
|

Do the right thing: but only if others do so

Abstract: Social norms play an important role in individual decision making. We argue that two different expectations influence our choice to obey a norm: what we expect others to do (empirical expectations) and what we believe others think we ought to do (normative expectations). Little is known about the relative importance of these two types of expectation in individuals' decisions, an issue that is particularly important when normative and empirical expectations are in conflict (e.g., systemic corruption, high crime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
430
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(458 citation statements)
references
References 47 publications
22
430
1
5
Order By: Relevance
“…In a related article on decision-making in a dictator game, Bicchieri and Xiao (2009) studied normative and empirical expectations. Normative expectations are what we believe others think we ought to do, 3 while empirical expectations are what we think others will do.…”
Section: Moral Opinionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a related article on decision-making in a dictator game, Bicchieri and Xiao (2009) studied normative and empirical expectations. Normative expectations are what we believe others think we ought to do, 3 while empirical expectations are what we think others will do.…”
Section: Moral Opinionsmentioning
confidence: 99%
“…A person's opinions of what he or she ought to do in a given situation are called "personal normative beliefs" (Bicchieri and Xiao 2009;Budd and Spencer 1985). In the current experiment, subjects participate in a public good game and report their personal normative beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that players follow descriptive norms that emerge during the game (see, Bicchieri and Xiao, 2009). In our case, Player C's decision is realized only when B chooses In; however, in doing so, B indicates that it is appropriate to choose a selfish option.…”
Section: Discussionmentioning
confidence: 99%
“…We would be able to explore the existence of social norms and attempt to test the hypothesis put forward by Bicchieri and Xiao (2008) that individuals tend to disobey a norm, such as sexual fidelity, when their empirical expectations about the actual behavior of the people in their social group do not match their normative expectations of how others think one should behave. In addition, we could try to measure the effect of the anticipated positive and negative social sanctions on individual decisions in order to better understand the mechanisms of social pressure and the role of different motives for compliance with norms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on the operational definitions of social norms has revealed that, in addition to believing that certain behavior is socially interpreted as the right way to act in a particular situation (normative expectations), individuals need to perceive that there is a substantial level of compliance with the norm (empirical expectations) in order to be motivated to obey it (Bicchieri 2006). Moreover, some experimental work has shown that individuals are more prone to violate the norm in situations in which they believe that only a small proportion of their social group actually comply with it, even if they also believe that most of the people in the group think that the rule should be followed (Bicchieri and Xiao 2008). In sum, the behavior of others is expected to play an important role in explaining individual actions.…”
Section: Social Interactions and The Behavior Of Othersmentioning
confidence: 99%